Forensic Medical Evaluation of Pregnant Cases: An Analysis of Trauma and Outcomes - Aydoğan, Halit Canberk; Yaşar Teke, Hacer; Arslan, Hanım Gökçe (The Bulletin of Legal Medicine, 2025)
Objective: Trauma during pregnancy poses significant risks to both the mother and the fetus. This study aims to retrospectively evaluate the forensic and medical aspects of cases involving pregnant individuals examined by forensic medicine.Methods: A retrospective analysis was conducted on 6,082 forensic cases admitted to the Department of Forensic Medicine at Ordu University Training and Research Hospital between January 1, 2019, and December 31, 2023. Twenty-five cases identified as pregnant during the incident were included. Evaluations were based on age, incident origin, forensic examination, emergency and obstetric assessments, interval between evaluations, gestational age, and miscarriage status.Results: The mean age of cases was 24 ± 5.89 years, and 72% were exposed to trauma from assault, with 83.3% linked to partner violence. Hyperemia (40%) was the most common traumatic sign, while extremities (40%) and the abdomen (35%) were the most frequently injured regions. The mean gestational age was 22.6 ± 8.10 weeks, with 64% showing no ultrasonographic pathologies. Retroplacental hematoma was the most common anomaly. Two cases (8%) required advanced treatment, including one miscarriage from anterior placental bleeding and one incomplete abortion due to firearm injury. A significant correlation was found between abdominal trauma and ultrasonographic findings (Phi = 0.55, p = 0.006).Conclusion: The study reveals that most pregnancy-related trauma cases are due to assault, with a significant portion linked to partner violence. Timely and accurate forensic reporting is vital in domestic violence cases for ensuring accountability.
Keywords: Pregnancy; Partner violence; Assault; Miscarriage